Redesain TPS Limbah B3 PT X: Studi Kasus Industri Ransum Pakan Hewan di Jawa Timur - Michel Adam Yudistira; Muhammad Abdus Salam Jawwad (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
PT X is an animal feed industry located in East Java that generates Hazardous and Toxic Substances (B3) waste. The industry has a Temporary Storage Facility (TPS) building for storing its waste. However, an evaluation based on Regulation Permen LHK no. 6 of 2021 shows several non-compliances in the design and waste storage procedures of the B3 waste TPS. This study is conducted to evaluate and redesign PT X's B3 waste TPS to address the identified non-compliances. The stages of redesigning PT X's B3 waste TPS include: 1) identifying B3 waste, 2) evaluating the existing condition of the B3 waste TPS, 3) redesigning the B3 waste TPS, and 4) describing the building design changes. The new B3 waste TPS is designed to store toxic, liquid, and flammable waste with building dimensions of 4.15 m x 2.25 m x 3.675 m. The redesigned B3 waste TPS complies with regulations more effectively and addresses previous shortcomings.